Performansi Pengering Ikan Aliran Alami memanfaatkan Energi Kombinasi Kolektor Surya dan Tungku Biomassa - Made Ricki Murti (Jurnal Energi Dan Manufaktur, 2010)
In a drying process usually used forced flow condition. The energy used a dryer is usually only a single type of energy. Thus,the study is conducted on the natural flow dryer system by using the chimney. The energy used as a dryer is solar energy andbiomass that can be used simultaneously or one turns in accordance with the needs and circumstances. Has done testing of aprototype natural flow dryers utilize a combination of solar collectors energy and biomass furnace. Testing is done threetimes a process by measuring the following: the inlet air temperature of the biomass furnace, the outlet air temperature of thebiomass furnace, the inlet air temperature of the solar collector, the outlet air temperature of the solar collector, airtemperature into the drying chamber, air temperature out of the drying chamber, the mass decreasing of dried material, andthe intensity of solar radiation. Data were collected at each interval of 30 minutes was followed by processing of these datato obtain system performance, then made in the form of performance versus time graph. Results obtained in the form ofdrying time is achieved for one-time drying process is 7,5 hours, the average Solar collector efficiency is 54.4%, the averagebiomass furnace efficiency is12.57 %, the average drying efficiency is 22%, and the average system total efficiency is 2,8%.